Guidance for the calculation of carbon brainprints of higher education institution activities - Parsons, David J.; Chatterton, Julia C. (Cranfield University, 2011)
This document is intended to provide a guide to assessing a carbon brainprint. It was developed as the project case studies were conducted, starting from a set of general principles and becoming more specific. It is guided by the principles used by the IPCC, PAS 2050:2008 and Carbon Trust good practice. However, a carbon brainprint is not an assessment of the life cycle greenhouse gas emission of a specific good or service. In particular, the emphasis is mainly on total changes in emissions, not the functional unit, and general estimates rather than product-specific ones may be required. The guidance covers definitions, basic principles, system boundaries, attribution, uncertainty analysis and the scope and limits of application of the method.
Keywords: carbon footprint; greenhouse gases; climate change; global warming; LCA; universities; research; training